(untitled) (Journal of Bio-Science, 2016)
Context: In vitro propagation or tissue culture of plants offers a rapid means of producing large quality of clonal planting stock and propagation that are difficult to establish conventionally. Biotechnological tools are important for multiplication and genetic enhancement of the plants by adopting techniques such as in vitro regeneration and genetic transformations. Objective: Effect of different plant growth regulators (PGRs) and their concentration on multiple shoot regeneration and callus formation was studied in Indigofera viscosa. Materials and Methods: In vitro plant regeneration was achieved in nodal and shoot tip explants. The explants were cultured on MS medium supplemented with BAP and NAA. Results: The nodal explants exhibited a greater number of healthy multiple shoots. The maximum callus induction was observed on MS medium supplemented with 1.5 mg L-1 2,4-D. NAA and BAP combination proved to be the most effective treatment for promoting shoot multiplication. IBA was found to be the best rooting hormone than IAA or NAA. The plantlets showed high survival rate in the soil. Conclusion: The present investigation clearly established and demonstrated the method of obtaining the new plantlets in Indigofera viscosa supported by different hormone concentrations J. bio-sci. 22: 53-58, 2014